Formulation Approaches for Improving the Dissolution Behavior and Bioavailability of Tolvaptan Using SMEDDS - Jong-Hwa Lee; Gye-Won Lee (MDPI AG, 2022)
Tolvaptan, a selective vasopressin receptor antagonist, is a Class IV agent of Biopharmaceutical Classification System (BCS). To improve bioavailability after oral administration, the new tolvaptan-loaded self-microemulsifying drug delivery system (SMEDDS) was further optimized using a "design of the experiment (DoE)" including components of D-optional mixture design. Based on a solubility study of tolvaptan in various oils, surfactants, and cosurfactants, Capryol® 90, Tween 20, and Transcutol® HP [or polyethylene glycol 200 (PEG 200)] were finally selected for optimization of tolvaptan-loaded SMEDDS formulations. The fitting models of, and poly-nominal equations for, all response variables were acceptable, as revealed by analysis of variance (ANOVA, R2 > 0.900, p < 0.0001). The optimized formulations A-1 (Capryol® 90/Tween 20/Transcutol® HP = 10%/70%/20% w/w) and B-1 (Capryol® 90/Tween 20/PEG 200 = 10%/70%/20% w/w) with desirabilities of 0.905 and 1.000, respectively, showed low droplet size and the dissolution rate exceeded 95% at 15 and 60 min. The tolvaptan-loaded SMEDDS remained stable for 3 months under accelerated conditions, thus with no change in any of content, color, particle size, or dissolution rate. In a rat pharmacokinetic study, the bioavailability of formulations A-1 (16.6%) and B-1 (11.5%) were 23-33-fold higher than that of raw tolvaptan powder (0.5%). Thus, the use of "quality by design (QbD)" during development of tolvaptan-loaded SMEDDS improved the dissolution rate and oral drug bioavailability.